Confronting HPV: Insights and Solutions (IntechOpen, 2025)
Human papillomavirus (HPV) is a global health concern that impacts millions, contributing to conditions ranging from benign warts to life-threatening cancers. Despite the availability of vaccines and advancements in treatment, HPV continues to pose significant public health challenges worldwide. Confronting HPV - Insights and Solutions offers an in-depth exploration of the virus, providing the latest research and expert perspectives on its epidemiology, treatment, and prevention strategies. This comprehensive resource tackles critical questions surrounding HPV, addressing both its biological complexity and the social impact of the disease. From understanding the spread of the virus and its role in various cancers to examining the effectiveness of vaccination programs, this book equips healthcare professionals, researchers, and public health advocates with the knowledge needed to fight HPV more effectively. In addition to discussing clinical and preventive approaches, Confronting HPV - Insights and Solutions highlights the importance of its vaccine. With actionable insights and forward-thinking solutions, this book serves as an essential guide for anyone working to reduce the burden of HPV on individuals and communities alike.